2020
DOI: 10.1097/ccm.0000000000004122
|View full text |Cite
|
Sign up to set email alerts
|

Critical Illness Factors Associated With Long-Term Mortality and Health-Related Quality of Life Morbidity Following Community-Acquired Pediatric Septic Shock*

Abstract: Objectives: A companion article reports the trajectory of long-term mortality and significant health-related quality of life disability among children encountering septic shock. In this article, the investigators examine critical illness factors associated with these adverse outcomes. Design: Prospective, cohort-outcome study, conducted 2013–2017. Setting: Twelve United States academic PICUs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 51 publications
3
97
0
3
Order By: Relevance
“…95 Lower quality-of-life scores were associated with multiorgan dysfunction, renal replacement therapy, ECMO or cardiopulmonary resuscitation, and duration of mechanical ventilation and inotropes. 96 Similar findings were observed internationally. 11 Given that most children with sepsis are younger than 10 years of age, the long-term impact of sepsis sequelae on children, their families, and society cannot be emphasized enough.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…95 Lower quality-of-life scores were associated with multiorgan dysfunction, renal replacement therapy, ECMO or cardiopulmonary resuscitation, and duration of mechanical ventilation and inotropes. 96 Similar findings were observed internationally. 11 Given that most children with sepsis are younger than 10 years of age, the long-term impact of sepsis sequelae on children, their families, and society cannot be emphasized enough.…”
Section: Discussionsupporting
confidence: 73%
“…Of concern, more than one‐third of pediatric survivors had not regained their baseline health‐related quality of life one year after an episode of community‐acquired sepsis 95 . Lower quality‐of‐life scores were associated with multiorgan dysfunction, renal replacement therapy, ECMO or cardiopulmonary resuscitation, and duration of mechanical ventilation and inotropes 96 . Similar findings were observed internationally 11 .…”
Section: Discussionmentioning
confidence: 63%
“…We found that performing the needs assessment, in particular demonstrating the high estimated rate of new morbidity in sepsis survivors in historical patients cared for at our hospital, was helpful in justifying the costs of the program. In the Life After Pediatric Sepsis Evaluation study, it was shown that changes in FSS or Pediatric Overall Performance Category score between days 1 and 7 were highly predictive of death or severe deterioration in HRQL 3 months after sepsis (12). Incorporating these scores as screening tools to identify those most likely to benefit from a sepsis follow-up program might further refine the appropriate target population and limit costs associated with a program like this.…”
Section: Discussionmentioning
confidence: 99%
“…The largest decrease was seen in the first month after discharge with 50% of survivors below baseline HRQL, with some recovery that plateaued between 3 months and 1 year after discharge. Children with more organ dysfunction and those requiring higher levels of vasoactive infusion support were at highest risk of serious deterioration in HRQL (12). Furthermore, children without chronic comorbidities were disproportionately impacted by deterioration in HRQL (13).…”
Section: Introductionmentioning
confidence: 99%
“…Most post-neonatal pediatric intensive care unit (PICU) admissions account for majority of pediatric deaths in developed countries, especially in the United States ( 1 , 2 ). However, recent technological advances in pediatric research have significantly reduced the mortality rates among PICU admissions by prolonging the life of critically ill patients ( 3 5 ). Three recent multicenter studies have reported a decline in PICU mortality rates of ~<3% in western countries ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%